Analyzing Factors Determining Clothing Interest and Purchase Intention Towards Everyday Pajamas Fashion Products - Muharam, Ilham; Qastharin, Annisa Rahmani (Journal of Business and Management, 2021)
The trend of Everyday pajamas has recently become popular in the fashion world. Along with the growth of the trend, there are a large number of brands and also numerous everyday pajamas products within the market. This situation shows that there is high competition within the market of everyday pajamas, which could make business experience a reduction in its profits. Facing this situation, brands need to understand consumer’s clothing interest and purchase intention concept to develop marketing strategies to further help brands being competitive referring to the current competition within the industry. This research aims to identify factors influencing clothing interest and purchase intention in everyday pajamas products. To analyze the data result from 215 respondents, the writer uses Partial Least Square Structural Equation Modelling (PLS-SEM) with SmartPLS tool. The result finds that Attitude and Perceived behavioral control positively and significantly influence purchase intention towards everyday pajamas fashion products. Attitude within this research has become the most influencing factor towards everyday pajamas. On the other hand, need for uniqueness, WOM, brand image, and perceived quality become the factors that influence clothing interest. The findings of this research are expected to give insightful information for brands and for future study.Keywords: Everyday Pajamas, Competition, Clothing Interest, Purchase Intention, PLS-SEM